GAYA BAHASA PERBANDINGAN DALAM NOVEL SIHIR PAMBAYUN KARYA JOKO SANTOSO - Agus Supriyanto (LPPM UNISDA, 2017)
The purpose of this study are to this style of figurative language in Sihir Pambayun novel by Joko Santoso(a) Describe the personification style, (b) describe the metaphor, and (c) the style Simile. The research uses descriptive qualitative method-semoitik structuralism and hermeneutictechniques. This is done because analyzing a novel is hard to avoid the use of integratedmethods so that it is impossible to use. Study the style offigurative language (figurative) are purposely created to obtain the aesthetic effect todescribe the background of the story.